2012
DOI: 10.4103/0970-4388.105014
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal and Dentoalveolar changes concurrent to use of Twin Block appliance in Class II division I cases with a deficient mandible: A cephalometric study

Abstract: Most of Class II malocclusions are due to underdeveloped mandible with increased overjet and overbite. Lack of incisal contact results in the extrusion of the upper and lower anterior dentoalveolar complex, which helps to lock the mandible and prevent its normal growth and development, and this abnormality, is exaggerated by soft tissue imbalance. The purpose of present study was to cephalometrically evaluate skeletal and dentoalveolar changes following the use of Twin-Block appliance in 10 growing children of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
13
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 0 publications
10
13
0
2
Order By: Relevance
“…It correlates with the findings with the that of Tiziano and Lorenzo [13] and Kevin and Jean [14]. The skeletal and dental effects of Twin block therapy on Indian population were done by Sharma et al, [15]. The subjects selected in that study are all in mixed dentition period with active growth potential.…”
Section: Skeletal Changessupporting
confidence: 70%
“…It correlates with the findings with the that of Tiziano and Lorenzo [13] and Kevin and Jean [14]. The skeletal and dental effects of Twin block therapy on Indian population were done by Sharma et al, [15]. The subjects selected in that study are all in mixed dentition period with active growth potential.…”
Section: Skeletal Changessupporting
confidence: 70%
“…Such findings are in line with a study performed by Sharma et al 20 that indicated a significant increase in the interincisal angle in cases of orthodontic treatment utilising twin block appliances.…”
Section: 22supporting
confidence: 93%
“…Several studies reported significant proclination of mandibular incisors after treatment with twin block appliances, while the mandibular incisors remain stable in their position. 20 This result may be explained by the design of the twin block appliance. The use of an acrylic cover on mandibular incisors and the eyelet clasps produce rigid retention on the labial lower jaw, as well as the use of sounthend clasps by Tarvade.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation
“…But some studies observed some headgear effect resulting in slight inhibition of forward maxillary growth. 16, 21 Singh and Hodge also concluded that Twin block appliances along with extra oral traction causes growth modulation in specific regions of midfacial complex and changes position of mandible. 25 Lower facial height also increased with twin block therapy, 16,17,19 but Nicole et al demonstrated good vertical control on mandibular plane angle with twin block appliance therapy as compared to Herbst, Bionator and MARA appliances.…”
Section: Skeletal Effects Of Twin Blocksmentioning
confidence: 99%